Aspectos relacionados à seletividade do fomesafen na cultura do algodoeiro - Oliveira Neto, Antonio Mendes de (2014)
Although the herbicide Fomesafen is used in the pre-emergence phase in cotton crops in several countries, scanty information on its selectivity is still scarce in Brazil. Due to the flower composition of weeds in cotton crops, fomesafen is an interesting alternative for chemical control of weeds in the pre-emergence phase. Current assay evaluates the response of cotton plants to the application of fomesafen either alone or with other pre-emergent herbicides in greenhouse and field conditions. Cotton cultivars respond differently to the application of the herbicide fomesafen alone or in combination with pre-emergence herbicides diuron, prometryn and trifluralin in greenhouse conditions. The application of fomesafen in soils with low clay and organic matter rates may cause the death of seedlings and compromise the establishment of culture stand. The type of crop waste left on the soil in the no-tillage system may affect the selectivity of fomesafen for cotton. The application of clomazone alone and the application of the mixture clomazone + fomesafen (1.0 + 0.45 kg ha-1) with or without herbicides diuron (1.25 kg ha-1), prometryn (1.25 kg ha-1), trifluralin (1.80 kg ha-1) and s-metolachlor (0.77 kg ha-1) were selective for cotton crop cultivar DP 555 BG RR. Similarly, the application of the herbicide fomesafen alone or mixed with herbicides prometryn, diuron, trifluralin and s-metolachlor during pre-emergence was selective for cotton. The application of fomesafen alone during pre-emergence followed by s-metolachlor application in early post-emergence was selective for cotton. However, the use of tank mixtures involving the herbicide fomesafen during pre-emergence supplemented with s-metolachlor application in early post-emergence was, as a rule, not selective for cotton.